Qualitative findings from a systematic review: Visual arts engagement for adults with mental health conditions1. (1st November 2020) - Tomlinson, Alan; Lane, Jack; Julier, Guy; Grigsby-Duffy, Lily; Payne, Annette; Mansfield, Louise; Kay, Tess; John, Alistair; Meads, Catherine; Daykin, Norma; Golding, Alex; Victor, Christina
This article reports on an investigation of the effects of 'visual arts'-based programmes on subjective well-being (SWB) outcomes for adults with mental health conditions. In a systematic review, electronic databases were searched for articles published from January 2007 to April 2017. Grey literature completed from January 2014 to April 2017 was also considered. Six published articles of mostly moderate quality and six evaluation reports (grey literature) covering a wide range of visual arts practice, population groups and settings were included. Key themes emerged connected to the concept of 'bonding', sense of belonging, appreciation of self-identity and the confidence that engagement in visual arts can facilitate. The overall conclusion supports that visual arts have the potential to enhance the SWB of adults with mental health conditions. The evidence is relatively limited in terms of scope and quality ‐ increased funding across sectors should be secured to support more extensive and long-term research.